Optimizing Staffing Models and Team Structure : For Dignified, Person-Centered Care Amidst Demographic Change - World Bank Group (World Bank, Washington, DC, 2019)
Rapid demographic change, particularly aging populations and a growing burden of chronic disease and multi-morbidity, are straining even the most sophisticated primary health systems. Many frontline health systems are ill-equipped to respond to these challenges, constrained by low health worker availability and fragmented service provision. Innovative models for staffing and organizing frontline health services are needed that foster interdisciplinary collaboration, coordination of care, and person-centered approaches to help people remain healthy and active in their communities as they age.